Mombolosuako Traditional Marriage Dynamics: Between Tolaki Muslim Majority and Muslim Minorities in Konawe District, Indonesia - Ahmad, Ahmad; Iqbal, Muhammad; Waeno, Mahamadaree; Hajar, Siti; Syatar, Abdul (IAIN Manado, 2024)
This study examines the dynamics of the Mombolosuako (elopement) tradition among the Tolaki ethnic group in Southeast Sulawesi, Indonesia, focusing on its practice in religiously diverse communities. This research specifically compares the implementation and acceptance of this tradition between the Muslim-majority Anggaberi District and Catholic-majority Puasana Village in Konawe Regency. Using a qualitative approach with a comparative case study design, data were collected through in-depth interviews with 16 key informants, field observations, and document analysis analyzed through Interpretative Phenomenological Analysis (IPA). The findings reveal that in Anggaberi, where Muslims and Tolaki are the majority, Mombolosuako is practiced as a non-normal marriage from cultural identity although some consider it contrary to Islamic teachings. This practice is supported by Regional Regulation No. 1 of 2018 concerning the Implementation of Sara Merapu Customary Law of the Tolaki Tribe. Conversely, in Puasana, where Muslims and Tolaki are minorities, this tradition is neither known nor practiced. This indicates that diversity can reduce the role of customs in social structures. This research emphasizes the importance of adaptive and contextual regulatory approaches in multicultural societies, so that customary policies can balance between preserving traditions and dynamic social needs. These findings provide insights for policymakers and academics in designing more inclusive customary policies and add to the literature on the interaction between customary law, religion, and formal regulations in plural societies.